Medio ambiente y acciones populares en Colombia : Un estudio empírico (2017)
This paper presents the results of an empirical study that systematized environmental judicial opinions handed down by Colombia's highest administrative Court-Consejo de Estado- over a 17-year period (1998-2015). Thanks to a research grant, the authors and a team of coders systematized, using state-of-The art content analysis methodologies, more than 250 opinions handed down by Colombia's highest administrative Court. The results presented in this paper show the most important trends of collective environmental litigation in Colombia: Types of plaintiffs and defendants; type of environmental resources involved in the case; plaintiffs' success rates; most litigious regions and cities; overall effects of economic incentives on the type of litigation, among several other subjects. This paper concludes that collective environmental litigation has been instrumental to protect environmental resources in Colombia, one the most biodiverse countries in the world. Finally, the paper concludes that the elimination in 2011 of the economic incentive in favor of litigants did not favor public interest litigation.